UV photoelectron spectroscopy at near ambient pressures: mapping valence band electronic structure changes from Cu to CuO - Roy, Kanak; Gopinath, Chinnakonda S. (Analytical Chemistry, 2014)
Valence band (VB) changes and hence electronic structure evolution was directly observed with low kinetic energy (KE) electrons at near ambient pressure (NAP) conditions with He I photon source in a custom built laboratory ambient pressure photoelectron spectrometer (Lab-APPES). Polycrystalline Cu surfaces were gradually oxidized in O-2 to Cu2O, to a mixture of Cu2O + CuO, and finally to CuO between 300 and 625 K and at NAP. Typical VB features for Cu, Cu2O, and CuO were observed, and the results corroborate well with core level and Auger spectral changes. High mean free path associated with low KE electrons, very low or no inelastic scattering, and effective pumping and the design of electrostatic lens regime help to minimize the electron attenuation at NAP conditions. The present results extend the capabilities of the APPES tool to explore the in situ evolution of electronic structure of materials at NAP and high temperatures.